The effect of ovariectomy on rat vaginal tissue contractility and histomorphology - ERCAN, FERİHA; TARCAN, TUFAN (ELSEVIER SCI LTD, 2006)
Introduction. Ovarian hormones have an important role in age-related genital arousal disorders; however, our knowledge regarding possible vaginal wall morphology and contractility changes in low-hormonal states is limited. Aims. To investigate morphological and functional alterations in the vaginal tissue in a rat ovariectomy model and to show the differences between proximal and distal vagina. Methods. Six weeks following ovariectomy, vaginal tissues were examined under light and electron microscopy. Circularly cut distal and proximal tissues were studied in the organ bath tinder isometric tension and compared with age-matched controls. Contractile responses to electrical field stimulation (EFS), phenylephrine, carbachol, and the effects of alpha-1 and alpha-2 blockade on EFS-induced contractility were investigated. Relaxation responses to EFS and vardenafil were investigated in precontracted strips. Main Outcome Measures. Differences between control and ovariectomy groups in terms of vaginal tissue contractility, and histomorphological properties. Results. Distal vagina showed different epithelial characteristics and a better-developed muscularis compared with proximal vagina. Ovariectomy caused thinning of the epithelium, severe degeneration in epithelial architecture, and smooth muscle atrophy. Contraction and relaxation responses of distal strips were significantly lower in ovariectomized rats. Contractile responses to neuropharmacological stimulation were insignificant in proximal strips of both groups. EFS-induced contractions in distal strips diminished significantly after alpha-1 and alpha-2 adrenergic blockade. EFS caused frequency-dependent relaxation responses in precontracted distal strips, which were significantly decreased after nitric oxide synthase inhibition. Conclusions. Ovariectomy causes significant alteration in rat vaginal tissue morphology and contractility. Contraction and relaxation responses of distal vagina are significantly greater compared with morphologically distinct proximal vagina. Alpha-1 and alpha-2 receptors are the main mediators of contraction in distal rat vaginal tissue whereas nitric oxide pathway may have at least a partial role in relaxation. Main mediators of the rat vaginal tissue relaxation and the effect of ovariectomy on this regulation are yet to be defined.
Keywords: neurophysiological studies of sexual function; pharmacological studies in sexual function; animal models; CYCLASE-ACTIVATING POLYPEPTIDE; FEMALE SEXUAL DYSFUNCTION; NITRIC-OXIDE SYNTHASE; BLOOD-FLOW; NERVE-FIBERS; INNERVATION; RESPONSES; HORMONES; TRACT; VIP